Ease of Access and Perception of Security in the Decision to Use Wondr by BNI: The Role of Digital Accounting (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
This study aims to examine the effect of accessibility and perceived security on the decision to use the Wondr by BNI mobile banking service and to analyze the moderating role of digital accounting. A quantitative approach was employed using purposive sampling involving 112 respondents who were BNI customers using the Wondr by BNI application. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS software. The results indicate that accessibility has a positive and significant effect on the decision to use mobile banking, with a path coefficient of 0.991, T-Statistic of 173.609, and P-Value of 0.000. In contrast, perceived security does not significantly influence the usage decision (T-Statistic 0.384; P-Value 0.701). Digital accounting also shows no significant effect on usage decisions (T-Statistic 0.066; P-Value 0.947) and fails to moderate the relationship between accessibility, perceived security, and the decision to use mobile banking services. The R-Square value of 0.982 indicates that the model has very strong explanatory power. These findings highlight that accessibility is the most influential factor affecting customers’ decisions to use the Wondr by BNI mobile banking service.